Evaluating Incentive Policies on RT/RW Performance in Community Services - Rahma; Angelina E Rumengan; Bambang Satriawan (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study evaluates the incentive policy for neighborhood leaders (RT/RW) in Tanjungpinang City and its impact on community service performance, with community participation as a moderating variable. Despite policy implementation, questions remain regarding its effectiveness in enhancing grassroots service delivery due to perceived mismatches between compensation, workload, and procedural transparency. Using a mixed-methods approach, quantitative data were collected from 271 RT/RW leaders via structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling, complemented by qualitative interviews and focus group discussions. Results indicate that incentive-job fit, policy clarity, fairness, transparency in distribution, and overall policy effectiveness significantly and positively influence RT/RW performance. Furthermore, community participation significantly strengthens all these relationships, acting as a vital social catalyst. The findings highlight that financial incentives alone are insufficient; their success depends on multidimensional policy design integrated with active citizen engagement. This research contributes to micro-governance literature by empirically validating the moderating role of community participation in policy implementation. Practically, it recommends transitioning from flat-rate incentives to performance-based, transparent, and participatory models to sustainably improve grassroots public services.